The experience of foot problems and decisions to access foot care in patients with rheumatoid arthritis: a qualitative study. Issue 1 (December 2017) - Wilson, Oonagh; Kirwan, John; Dures, Emma; Quest, Enid; Hewlett, Sarah
Abstract Background Although foot problems are common in rheumatoid arthritis (RA), the consequences of foot problems from the patient perspective have not been fully explored. The aims of this study were to explore the experience of foot problems and decisions to access foot care services or not in patients with RA. Methods Semi structured, one-to-one interviews with patients recruited from 2 UK rheumatology units, purposively sampled for self-reported foot problems and a range of personal/disease characteristics. Inductive thematic analysis was used, with rigour provided by multiple independent analysers. Emerging themes were discussed and agreed by all authors. Results Twelve patients participated: 7 female; mean age 56 years (29–72); mean disease duration 12 years (2–27), 5 had accessed foot care services. The 'Impact' of foot problems was substantial and formed the underpinning theme, comprising three organising themes: 'Foot symptoms'; 'Consequences'; and 'Cost'. Foot symptoms such as pain and numbness required self-management, and affected daily life (walking, working) leading to social and emotional costs. The global theme, 'Decision to access foot care or not', also comprised three organising themes: 'Access perceived unnecessary' (no problem, can cope); 'Access hindered by patients' perception'; and 'Access supported by patient and clinician'. Decisions to access foot care or not were complex and influenced by patient beliefs regarding possible treatments and how to access these, and hindered by patient perceptions that their feet were ignored by rheumatology clinicians. Positive experience of foot care encouraged continued utilisation but negative experiences contributed to patients' decisions to discontinue foot care services. Conclusions Foot problems are important issues for patients and impact on many aspects of their physical, social and emotional lives. Patients who had accessed foot care services prioritised their foot problems as an important health care need. However, for others who would like foot care services, personal knowledge and values, and perceived barriers in clinical practice, appear to interact to inhibit foot care access. The extent which these interactions affect overall access to foot care in RA patients in general now needs to be quantified to help to inform and improve the effectiveness of the organisation and delivery of foot care.